2018
DOI: 10.3390/math6050066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Viral and Cytokine Delays on Dynamics of Autoimmunity

Abstract: Abstract:A major contribution to the onset and development of autoimmune disease is known to come from infections. An important practical problem is identifying the precise mechanism by which the breakdown of immune tolerance as a result of immune response to infection leads to autoimmunity. In this paper, we develop a mathematical model of immune response to a viral infection, which includes T cells with different activation thresholds, regulatory T cells (Tregs), and a cytokine mediating immune dynamics. Par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…However, earlier work of Iwami et al [10,11] has shown that, while this behaviour can be observed for both types of growth functions in the absence of infection or immune reaction, their specific functional form does have a significant effect on the overall dynamics of autoimmune disease. Thus, we have chosen to use a logistic form for the growth function of healthy organ cells, in agreement with Iwami et al [10] and our earlier work on autoimmunity [34][35][36][37][38][39][40].…”
Section: Deterministic Mathematical Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…However, earlier work of Iwami et al [10,11] has shown that, while this behaviour can be observed for both types of growth functions in the absence of infection or immune reaction, their specific functional form does have a significant effect on the overall dynamics of autoimmune disease. Thus, we have chosen to use a logistic form for the growth function of healthy organ cells, in agreement with Iwami et al [10] and our earlier work on autoimmunity [34][35][36][37][38][39][40].…”
Section: Deterministic Mathematical Modelmentioning
confidence: 90%
“…Blyuss and Nicholson [34,35] used a TAT-based model to investigate autoimmunity arising through a mechanism of molecular mimicry from immune response to a viral infection. To capture a dynamical regime where autoimmunity arises as a by-product of viral infection but after that initial infection has already been cleared by the immune system, Fatehi et al [36][37][38][39][40] developed this model further by including cytokines mediating T cell proliferation, as well as time delays associated with various aspects of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…While regulatory T cells may block the expression of IL-2 by T cells by suppressing IL-2 mRNA, thus restricting T cell proliferation [82,83,84], similarly to other studies that analysed the role of IL-2 in T cell dynamics [85,86,87], we do not explicitly include this mechanism in our model not to increase its complexity. This effect can, however, be included as an additional term (−γT reg I) in the equation for IL-2 [24,25], though our earlier analysis of an analogous model has shown that this effect may be smaller compared to other contributions, such as the suppressive effect of regulatory T cells on autoreactive T cells [47].…”
Section: Deterministic Modelmentioning
confidence: 99%
“…This has also provided practically important insights into how variance of stochastic oscillations depends on different parameters, which is very important for comparison with clinical observations of individual realisations of progression of autoimmune disease. A complementary analysis has been performed by Fatehi et al [47,48] to investigate the role played by time delays associated with different aspects of immune response and virus cycle dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this model we assume that T nor and T aut produce IL-2 at rates σ 1 and σ 2 . On the other hand, whilst regulatory T cells do not produce IL-2, similar to other T cells they need this cytokine for their activation and proliferation [94,95]. Thus, we assume that IL-2 promotes proliferation of T reg , T nor and T aut at rates ρ 1 , ρ 2 and ρ 3 , respectively.…”
Section: Model Derivationmentioning
confidence: 99%